Exploring the Efficacy of the Discourse Based Approach on Teaching Business English in Algeria: A Needs Analysis Perspective with Master1 Students at Tlemcen University - Larbi, Qwider; Ben Ahmed, Mohammed (Future Science, 2025)
This study investigates the pedagogical value of a discourse-based approach in teaching Business English within an English for Specific Purposes (ESP) context. It focuses on how this approach enhances learners’ acquisition, contextual use, and retention of business-related vocabulary, while also fostering greater communicative competence. A mixed-methods design was employed, combining both descriptive and experimental techniques to collect and analyze data. The participants were Master 1 Business English students who underwent a 12-week instructional program integrating discourse analysis principles and authentic materials. Findings indicate that students exposed to the discourse-based methodology outperformed those taught using traditional methods, particularly in their ability to understand and apply business vocabulary in real-world communicative settings. Moreover, learners reported increased confidence and fluency in using business language appropriately across intercultural and professional contexts. These results highlight the discourse-based approach as a promising strategy for developing both linguistic and pragmatic competencies, recommending its broader adoption in Business English instruction.